China Strategic Roles Over Artic Region After U.S- Russia Diplomatic Drift in 2015 Crimean Crisis (State Islamic Institute of Kudus (IAIN Kudus), 2018)
Arctic regions, on the northern pole of the earth, have attracted many countries with various interests. The United States, Russia and several Scandinavian countries, each have claims over its regions, which are known to have abundance natural resource. Besides its potential, Artic also become the most vulnerable area whom embrace the direct impact of global warming. Russia as a country with wide territorial borders directly to Arctic region, certainly has a big role in this region. But, Rusia’s relationship with several Western countries such as the US and Canada had not been in a good condition in 2015, since the Crimean crisis. Several psywar through mass media, even led Russian President Vladimir Putin decides to leave the G20 Annual Summit. Putin’s gesture somehow was seen as Russia implied response to the world related to the Crimea crisis which boldly stated that Russia was not afraid of the threat. The instability of Russia's relations with its neighboring countries which incidentally also borders the Arctic region opens the role of other countries to participate in this region, including China. This articles focused on describing out the China Strategic Policy in the Arctic region by identifying its national interests, and what policies China has taken to achieve its goals. The concept of securitization developed by Barry Buzan and Ole Waever is used as an analytical tool to identify China's strategic role in the Arctic region Keywords: China, securitization, national interest , Artic Region